Effectiveness of cognitive behavior therapy in tobacco cessation at a dental setting: A hospital-based randomized controlled trial - A Leena Selvamary; M B Aswath Narayanan; Jayanthi Doss; S G Ramesh Kumar (Wolters Kluwer Medknow Publications, 2016)
Introduction: Tobacco use continues to be the leading global cause of preventable death. Dental health professionals play a significant role in the intervention of the tobacco-related epidemic. Aim: The aim of this study was to compare the effectiveness of health education (HE) alone and HE with cognitive behavior therapy (CBT) at a dental tertiary referral unit of South India. Materials and Methods: Self-reported quit attempt was assessed and the sample size was estimated at 194. Tobacco users who met the inclusion criteria were randomly assigned to one of the two groups - HE only and HE with CBT. Age, sex, socioeconomic status, form of tobacco usage, alcohol usage, addiction and stage of motivation, knowledge, attitude, and behavior regarding tobacco use, and ill effects were assessed at baseline. Follow-up was for 6 months (2nd, 6th, 12th, and 24th weeks) to assess reduced use, quit attempt, point prevalence abstinence, continuous abstinence, lapse, relapse, and attrition rates in each visit. The self-reported quit rates were validated using the standardized cotinine test. Pearson's Chi-square test was used to determine the effectiveness of intervention. Results: Continuous abstinence was significantly high in CBT. Reduced use and point prevalence abstinence were significantly higher in HE. Quit attempt in both the groups was equal showing no statistical significance. Attrition was significantly higher in HE compared to CBT. Conclusion: CBT plays a vital role in achieving continuous abstinence, overcoming social factors, and reducing lapse among the tobacco users.